Negotiating Spiritual Identity: Islamic Education Strategies in Adolescents’ Digital Lives - M. Fakhrur Rizal; Ibnu Da'i Munis; Irfan Musonif (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2026)
The rapid expansion of digital technology has reshaped adolescents’ social interactions, knowledge construction, and identity formation, raising concerns about the sustainability of spiritual identity in digitally mediated environments. This study examines how Islamic Religious Education (Pendidikan Agama Islam/PAI) contributes to adolescents’ spiritual identity formation in the digital era. A qualitative descriptive case study was conducted in a public junior high school in Indonesia from January to February 2026. Data were collected through in-depth interviews, participant observation, and document analysis involving school leaders, teachers, and students, and analyzed inductively using an interactive model. The findings reveal three interconnected patterns: (1) contextual adaptation of Islamic teachings to digital realities, (2) experiential-reflective learning practices fostering critical awareness of digital behavior, and (3) ethical modeling supported by institutional structures. These patterns indicate that spiritual identity emerges through the interaction between pedagogy, lived digital experience, and school culture. This study proposes a situated model of spiritual identity formation, positioning religious education as a mediating space for negotiating values within digital contexts. The findings highlight the potential of PAI as an adaptive pedagogical framework that integrates religious values with contemporary digital life